2013
DOI: 10.1614/ws-d-12-00173.1
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Simazine andS-Metolachlor to Soils from a Chronosequence of Turfgrass Systems

Abstract: Pesticide sorption by soil is among the most sensitive input parameters in many pesticide-leaching models. For many pesticides, organic matter is the most important soil constituent influencing pesticide sorption. Increased fertility, irrigation, and mowing associated with highly maintained turfgrass areas result in constant deposition of organic material, creating a soil system that can change drastically with time. Changes in soil characteristics could affect the environmental fate of pesticides applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…This also indicates that adsorption process was reversible. The flubendiamide K d values were generally smaller than the K F of adsorption process in both two soil types because of nonlinearity in sorption, as reported in triazine herbicides by Gannon et al 2013. Adsorption-desorption studies with 1 % organic manure-treated soil revealed that Freundlich coefficient K F for adsorption process also increased in the two tested soils; 8.80 ml/g (organic manure-treated red soil) and 3.90 ml/g (organic manure-treated black soil) as compared to without amended soil.…”
Section: Resultsmentioning
confidence: 72%
“…This also indicates that adsorption process was reversible. The flubendiamide K d values were generally smaller than the K F of adsorption process in both two soil types because of nonlinearity in sorption, as reported in triazine herbicides by Gannon et al 2013. Adsorption-desorption studies with 1 % organic manure-treated soil revealed that Freundlich coefficient K F for adsorption process also increased in the two tested soils; 8.80 ml/g (organic manure-treated red soil) and 3.90 ml/g (organic manure-treated black soil) as compared to without amended soil.…”
Section: Resultsmentioning
confidence: 72%
“…However, high soil contents of clay and organic matter may also have positively influenced culture selectivity due to the lower herbicide availability for soil solution, since the sorption of atrazine (Procópio et al, 2001), (3) 1.00 1.00 1.00 1.00 1.00 1.00 1.00 1.00 5 isoxaflutole (Oliveira Jr et al, 2006) and S-metolachlor (Gannon et al, 2013) herbicides presents direct correlation with soil organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…Total marketable SR weight decline was more severe with the rainfall treatment, which could be attributed to low organic matter (0.68%) and clay (5.8%) content of the soil used in this study. S-metolachlor mobility in the soil solution has been reported to be affected by high organic matter content (>2.0%), clay mineral content and surface area (Nennemann et al, 2001;Senseman, 2007;Alletto et al, 2013;Gannon et al, 2013). In a peanut study, Cardina and Swann (1988) observed delayed emergence and reduced growth when irrigation followed metolachlor application at planting.…”
Section: Storage Root Yieldmentioning
confidence: 99%